Evaluation of Potential Oxidative Stress in Egyptian Patients with Acute Zinc Phosphide Poisoning and the Role of Vitamin C - Sagah, Ghada A.; Oreby, Merfat M.; Elgharabawy, Rehab M.; Ahmed Fathy, Amal S. (International Journal of Health Sciences, 2015)
Objective: To evaluate potential oxidative stress in patients with acute phosphide poisoning and the effect of vitamin C. Methods: Participants were females and divided into three groups; group I: healthy volunteers group II: healthy volunteers received vitamin C, group III: patients with acute phosphide poisoning received the supportive and symptomatic treatment and group IV: patients with acute phosphide poisoning received the supportive and symptomatic treatment in addition to vitamin C. All the participants were subjected to thorough history, clinical examination, ECG and laboratory investigations were carried on collected blood and gastric lavage samples on admission. Blood samples were divided into two parts, one for measurement of routine investigations and the second part was used for evaluation of malondialdehyde and total thiol levels before and after receiving the treatment regimen. Results: Most of the cases in this study were among the age group of 15-25 years, females, single, secondary school education, from rural areas and suicidal. All vital signs were within normal range and the most common complaint was vomiting and abdominal pain. All cases in this study showed normal routine investigations. The mean MDA levels after receiving treatment decreased significantly in groups II and IV. The mean total thiol levels increased significantly after receiving treatment in groups II and IV. Conclusion: It can be concluded that vitamin C has a potential benefit due to its antioxidant property on zinc phosphide induced-oxidative stress in acute zinc phosphide poisoned patients. Â